Comparison of Clinical Outcomes After Coronary Artery Bypass Grafting (CABG) With Percutaneous Coronary Intervention (PCI) in Coronary Artery Disease (CAD) Patients With Kidney Disorders: Systematic Review - Sandha, Dhiya Putri Aqilah; Sandy Tjang, Yanto; Faranita, Tri; Karina, Karina (Syntax Corporation Indonesia, 2024)
According to data from the WHO, heart disease continues to be the top cause of mortality worldwide. The 2018 Riskesdas shows that the prevalence of heart disease, including CAD, based on doctors' diagnoses in Indonesia is 1,5%. Management measures in CAD patients are CABG or PCI. The research design used in this study was a literature review using a systematic review method. A systematic literature review comparing CABG and PCI costs is needed to determine optimal therapeutic options in CAD patients. For articles published during the last ten years, a literature search was done using four databases: PubMed, SagePub, Google Scholar, and Science Direct. Based on the Preferred Reporting Items for Systematic Review and Meta-Analyses Protocol (PRISMA-P) 2020 protocol, a literature review was conducted. Eight texts in all met the inclusion and exclusion criteria for the study. Five literatures stating that CABG is better, two other literatures stating that there is no significant post-rehabilitation difference between CABG and PCI, and one literature stating that PCI has better survival after 5 years in CAD patients with impaired renal function. CABG is considered more effective and is recommended as the primary treatment option in CAD patients with a kidney disorder. Nevertheless, PCI can be utilized as an alternate therapy in CAD patients when kidney function and concomitant illnesses are considered.